Strategi UD. Sarjana Buah 88 dalam Meningkatkan Kesadaran Merek melalui Metode AISAS - Mahardika, Ega Adibrata; Panindias, Asmoro Nurhadi (Jayapangus Press, 2025)
This study aims to design and evaluate a digital marketing campaign strategy using the AISAS model (Attention, Interest, Search, Action, Share) to increase brand awareness of UD. Sarjana Buah 88, a micro, small, and medium enterprise (MSME) operating in the traditional fruit market in Yogyakarta. As social media usage continues to rise, conventional marketing strategies have become less effective, requiring adaptive approaches aligned with current digital consumer behavior. Descriptive qualitative method was employed, utilizing observation, interviews, documentation, and Instagram content analysis as data collection techniques. Visual content was developed based on each AISAS stage and implemented during a one-month campaign period. The success of the strategy measured using digital metrics such as increased viewers, profile visits, engagement rate, and positive interactions including comments and content saves. Survey results showed that product labeling influenced consumer interest, and visual design played a significant role in purchase decisions. The findings demonstrate that the AISAS-based strategy effectively captured attention, built interest, encouraged information-seeking behavior, triggered actions, and motivated users share their experiences. This campaign not only enhanced brand visibility and audience engagement of UD. Sarjana Buah 88 but also offers a replicable digital marketing framework for other MSMEs transitioning from conventional to digital systems.